Utilizing the Use of Google Trends to Discover The Architectural Attractiveness of a Place in Indonesia - Onie Dian Sanitha; Novera Kristianti; Theo Fransisco; Yunida Iashania (Universitas Atma Jaya Yogyakarta, 2023)
A person's memory of the image of a place is powerful, which is influenced by a uniqueness supported by continuity of information. Every visitor's image will be very subjectively evaluated through the internet information media. The challenge lies in subjective perception through internet media information which only sometimes leads to real quality due to perceptions formed from the continuity of information received. A shift in meaning allegedly led to a phenomenon of similar motivation between video game users and traveling for healing purposes. From the perspective of a Google search, the word